Guideline for Petch Sai Rung’Rose Apple Development of Farmers in Phetchaburi Province - แคนยุกต์ ณัฐชา (Journal of Humanities and Social Sciences, Rajapruk University, 2015)
This research aimed to study 1) Knowledge of Phetch Sai Rung’s rose apple. 2) Problems of growing Phetch Sai Rung’s rose apple. 3) Guideline for Phetch Sai Rung’Rose Apple Development of Farmers in Phetchaburi Province. The key informants were 5 farmers in Tambon Nong Sano, Amphoe Meuang; 5 farmers in Tambon Tha Raeng, Amphoe Tha Yang; and 5 farmers in Tambon Tha Mai Ruak, Amphoe Banlaem; 3 middleman and 2 agricultural technical officers. Data were collected using in-depth interviews approach. The data were analyzed according to the defined objectives based on theories and related research and descriptive prosonted. The results are as fallow: Originally Phetch Sai Rung’s rose apple is not native in Phetchaburi, which is cross between Red rose apple and Kahlapa. Brought from another place can yield great province and famous. Planting Phetch Sai Rung’s rose apple to get better result must be grown on river sediment a spacing 8×8 to 10×10 meter. Care is appropriate based on age and growth and care of post harvest handling. The problems to grow Phetch Sai Rung’s rose apple are the materials used to wrap, scaffolding and packaging. The research divided into 4 parts : Planting and development of Planting Phetch Sai Rung’s rose apple, attendance and development of attendance Phetch Sai Rung’s rose apple, marketing and development of marketing Phetch Sai Rung’s rose apple and the post harvest handling and development of post harvest handling Phetch Sai Rung’s rose apple. The results showed that Guidelines to development are change material wrapping, top cutting and packaging relevant agencies should come to assist.